Laser spectroscopy. Vol. 1, basic principles. (4th ed.) - Demtröder, W (Springer, 2017)
Keeping abreast of the latest techniques and applications, this new edition of the standard reference and graduate text on laser spectroscopy has been completely revised and expanded. While the general concept is unchanged, the new edition features a broad array of new material, including applications in chemical analysis, medical diagnostics, and engineering. No other book with such a broad scope is available. The author is one of the most renowned experts in this area. The book is well illustrated, and is supplemented by an extensive set of references. It will benefit all students and scientists working in the field.